Seychelles : Fourth and Fifth Reviews Under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Seychelles' Fourth and Fifth Reviews under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria. All performance criteria as of December 31, 2015, and June 30, 2016, were met, and the macroeconomic program remains broadly on track for the second half of the year. The structural agenda is proceeding, albeit with some technical delays. The IMF staff welcomes the authorities' commitment to the goal of a steady reduction in public debt over the medium term reflected in the draft 2017 budget.